PENGARUH BUTTERING PADA KUALITAS HASIL PENGELASAN DISSIMILAR BAHAN BAJA LUNAK AISI 1020 DENGAN BAJA TAHAN KARAT AISI 304 - Huda, Saiful; Waluyo, Joko; Yunianto, A. (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2006)
Welding is one of part importing in Manufacture process, because almost all manufacture product always get involve welding process, because of that process and welding result in manufacture process need to pay attention because this will be connected directly with quality of manufacture product. Mean while, as a judgmental in a production for stable in price is possible for using different material and has to weld by using welding process (dissimilar welding), in that hook, this research for knowing fisis characteristic and welding product mechanist between lowest carbon steel with endure corrosion steel by using direct dissimilar welding system and butter.In this research, was conducting welding by using low carbon steel material which have AISI standard 1020 and endure corrosion steel with ISI 304 series. Also AWS E 308 Welding was conducting by using SMAW system along with DC 80, 90 and 100 Ampere current variable. From that tarik tested that highest pull power had been result from welding with butter method and 90 ampere current is 44,79 Kg/mm2 and general result from tarik butter method test is better than direct method because all current variable has result bigger force than butter method. Mean while lowest pull power result on the direct welding with 100 amperes, its 43,3 kg/mm2. Mean while from the hardness result test that hardness distribution on the HAZ area and a good welding kernel result on the welding by using butter method with 90 ampere and direct method with 80 ampere. On the 100 ampere with butter method or hardness direct distribution not good because there are stepess on the hardness graphics that resulted. This point will be result in voltage concentration which is result in descending weld power.